AUTOMATIC TRANSFER SWITCH PANEL IN PLN ELECTRICITY AND POWER INVERTER 2000 WATT - Fora, Rony Haendra Rahwanto; Sunandar (Program Studi Teknik Elektro Universitas PGRI Adi Buana Surabaya, 2020)
In line with the development of science and technology today, especially in the field of electricity brought many changes in the use of electricity. Electricity is currently needed both industrial and non-industrial. Electricity needs are currently provided by PLN as the main power source. The flow of electricity from the electricity grid is not always continuous in its distribution, one day there must be a blackout that may be caused by interference with the transmission system or distribution system. To anticipate this outage, it is necessary to design an automatic control called an automatic transfer switch and to prepare a backup source, a 2000-watt power inverter. Automatic transfer switch is electrical equipment that functions as a controller of the process of switching the PLN electricity supply to the inverter power supply or vice versa automatically. In the operation of this automatic transfer switch can be operated manually and automatically. Where is in automatic mode, if there is a power outage on PLN this tool is useful for turning on and connecting the power inverter to the load automatically. When PLN revives, this tool will transfer the power source to the load from the power inverter to the PLN electricity. At this time technological advances are developing very rapidly, technology is an inspiration so that life in the world becomes lighter, easier and practical.